Caribbean Report 13-02-1989 - Whitehorne, Pat (anchor); Humphrey, Chester (interviewee); Manley, Michael (interviewee); Tomlinson, Alan (correspondent); Patrick, Soraya (correspondent); Berchoff, Pamela (interviewee); Batchelor, Steve (interviewee); Timmins, Jerry (correspondent); Ottey, Merlene (interviewee); Jackson, Grace (interviewee); Edwards, Andrew (correspondent) (The British Broadcasting Corporation, 1989)
In Jamaica, Michael Manley is to be sworn in as Prime Minister and the appointment of cabinet ministers is imminent. Interviews areto be held with two prominent Jamaicans living in Britain, Pamela Bechoff, lecturer and businesswoman, and Steve Bachelor, community worker and active PNP supporter on the future for Jamaicans. On the labor front, Chester Humphrey, Executive Secretary of Grenada Technical and Allied Workers Union is in London to garner the support of British unions. He claims that the Grenadian government is weakening the island's unions. In sports, interviews are held with Jamaicans, Merlene Ottey and Grace Jackson on their participation at the forth-coming European Indoor World Championship in Budapest.
1. Headline 00:00-00:40)
2. Michael Manley is to be sworn in as Prime Minister of Jamaica and the appointment of cabinet ministers is imminent (00:00-00:41)
3. Interviews with two prominent Jamaicans in Britain, Pamela Bechoff, lecturer and businesswoman, and Steve Bachelor, community worker and active PNP supporter on the future for Jamaicans (00:41-03:35)
4. Financial News (07:50-09:37)
Keywords: Elections -- Jamaica.; Labor unions -- Grenada.; Heads of state -- Jamaica.; European Indoor World Championships.